Beneficial impact of Baricitinib in COVID-19 moderate pneumonia; multicentre study. Issue 4 (October 2020) - Cantini, Fabrizio; Niccoli, Laura; Nannini, Carlotta; Matarrese, Daniela; Natale, Massimo Edoardo Di; Lotti, Pamela; Aquilini, Donatella; Landini, Giancarlo; Cimolato, Barbara; Pietro, Massimo Antonio Di; Trezzi, Michele; Stobbione, Paolo; et al.
Highlights: Baricitinib, an anti-JAK1/JAK2, reduces cytokine release and SARS-Co-V2 entry. In a retrospective multicenter study baricitinib reduces COVID-19 mortality rate. Baricitinib reduces intensive care unit admissions of COVID-19 pneumonia. Baricitinb reduces SARS-CoV-2 viral burden detected by nasopharyngeal swab. Baricitinib used for 2 weeks was not associated with serious adverse events. Graphical abstract: Image, graphical abstract